Inside Back Cover: Selective Oxidation of n‐Butane and Isobutane Catalyzed by Boron Nitride (ChemCatChem 12/2017). Issue 12 (22nd June 2017) - Venegas, Juan M.; Grant, Joseph T.; McDermott, William P.; Burt, Samuel P.; Micka, Jack; Carrero, Carlos A.; Hermans, Ive
Abstract : The Cover shows n ‐butane accompanied by an oxygen molecule traversing a boron nitride bridge. Upon crossing the bridge, n ‐butane is selectively transformed to 1‐butene while another, less fortunate molecule falls over the cliff to become CO2 .In their Full Paper, J. M. Venegas et al. report that hexagonal boron nitride selectively catalyzes the oxidative dehydrogenation of n ‐butane and isobutane to their respective olefins. Boron nitride is unique in that overoxidation of the desired olefins to carbon oxides is kept to a minimum and instead the minor side‐products are lighter olefins. The observed reaction kinetics point to a fundamentally different mechanism to that observed with conventional metal oxide catalysts. More information can be found in the Full Paper by J. M. Venegas et al. onpage 2118 in Issue 12, 2017 (DOI:10.1002/cctc.201601686 ).